2021
DOI: 10.3233/kca-210123
|View full text |Cite
|
Sign up to set email alerts
|

First-Line Immuno-Oncology Combinations for Metastatic Clear Cell Renal Cell Carcinoma (mRCC): A Systematic Review of Phase III Clinical Trials

Abstract: BACKGROUND: The introduction of immune checkpoint inhibitors rapidly changed treatment for patients with metastatic clear cell renal cell carcinoma (mRCC). First-line treatment now includes multiple immuno-oncology (IO) combinations that were approved over a short time period and were not directly compared in randomized clinical trials. Thus, clinicians face a challenge in individualizing first-line treatment to optimize clinical outcomes. OBJECTIVE: We sought to systematically review clinical outcomes for fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Combination therapy with an immune checkpoint inhibitor and a molecular targeted therapy is now the mainstay of treatment for patients with RCC, because of the excellent outcomes obtained in phase III clinical tri- als [1]. However, there are few data regarding the efficacy and safety of combination therapies, such as Ave plus axitinib, for patients with ESRD who are undergoing hemodialysis, because all of the key clinical trials excluded such patients [1][2][3]. Several case reports have presented the outcomes associated with combination therapies [4][5][6][7], but there have been no previous case reports of the use of Ave plus axitinib (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Combination therapy with an immune checkpoint inhibitor and a molecular targeted therapy is now the mainstay of treatment for patients with RCC, because of the excellent outcomes obtained in phase III clinical tri- als [1]. However, there are few data regarding the efficacy and safety of combination therapies, such as Ave plus axitinib, for patients with ESRD who are undergoing hemodialysis, because all of the key clinical trials excluded such patients [1][2][3]. Several case reports have presented the outcomes associated with combination therapies [4][5][6][7], but there have been no previous case reports of the use of Ave plus axitinib (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of the immunotherapy of various cancer types indicated that the frequency of adverse events is similar for patients with or without ESRD who are undergoing hemodialysis [8]. The characteristics of the Ave/axitinib combination might have contributed to the absence of high-grade irAEs, because the frequency of irAEs associated with Ave plus axitinib that required high-dose corticosteroid (≥40 mg/ day) has been reported to be lower (11.1%) than that associated with other combinations, such as ipilimumab (Ipi) plus nivolumab (Nivo) (29.1%) or Nivo plus cabozantinib (19.1%) [1]. However, close observation for adverse events is necessary because previous reports have suggested that there is a much higher risk of adverse events in patients with ESRD, especially if a molecular targeted agent is used [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation